Abdominal profiles of Barnacle Geese Branta leucopsis at staging areas in Iceland in May - Boyd, Hugh (Wildfowl, 2000)
The abdominal profiles of Barnacle Geese (Branta leucopsis) staging in northwest Iceland in spring were studied from 13-18 May 1978 and 25 April-10 May 1999 and on Islay, Scotland from 12-15 April 1979. Mean profile scores were highest in April 1979 and mid-May 1978. In 1999, the profile scores were lowest on 25-26 April. Mean daily rates of increase in the profiles of both sexes were greater between 26 April and 4 May than between 4 and 9 May. Fatter females tended to be paired to fatter males and fatter juveniles had fatter parents. Pairs still accompanied by young were fatter than most other pairs, which were usually fatter than single adults or juveniles. Differences in profile frequencies between districts were greatest on 25-26 April, soon after the geese had arrived: males and juveniles in small families were then in better condition than those with three or four young. On 4 and 9-10 May 1999, and 13-18 May 1978 there were no significant profile differences between members of small and larger families. Geese in the districts where they were thinnest initially fattened most rapidly.